1.2 kHz High‐Frequency Stimulation as a Rescue Therapy in Patients With Chronic Pain Refractory to Conventional Spinal Cord Stimulation. Issue 3 (14th September 2020) - Andrade, Pablo; Heiden, Petra; Visser‐Vandewalle, Veerle; Matis, Georgios
Abstract: Objectives: We aimed to investigate the efficacy of new subperception stimulation paradigms including 1.2 kHz‐high‐frequency stimulation (HFS) and advanced‐HFS field‐shaping algorithm (dorsal horn HFS [DHHFS]) in refractory cases which initially benefited from conventional spinal cord stimulation (SCS) and lost the effect throughout time. Materials and Methods: In the context of a rescue‐therapy, patients underwent externalization of the implanted SCS‐leads and were tested with multiple combinations of new SCS paradigms. Pain intensity was analyzed using the numeric rating scale (NRS), and data were collected preoperatively and at multiple postoperative follow‐ups. Results: Thirty‐seven patients underwent externalization of the leads. Mean preoperative NRS‐score was 8.1/10 points (SD ± 0.9) for the ON‐stimulation period. Patients received a combination of either tonic, burst and 1.2 kHz‐HFS, or burst and 1.2 kHz‐HFS, DHHFS, or 1.2 kHz‐HFS and DHHFS, or 1.2 kHz‐HFS alone. The mean postoperative NRS‐score after the testing‐phase was 3.8/10 points (SD ± 2.5), showing a 48.0% mean reduction ( p  < 0.001). In total, 29 patients reported a significant reduction above 50% in NRS‐scores and therefore were reimplanted with new generators that could deliver the new paradigms. Eight patients underwent full SCS‐system explantation. The patients who continued with the new paradigms ( n = 29) reported mean NRS‐scores of 3.5/10 points (SD ± 1.7) 12 months postoperatively, still showing a significant reduction of 43.3% when compared to preoperative scores ( p  < 0.001). Conclusion: Rescue‐therapy with combination of multiple waveforms, including tonic, burst, 1.2 kHz‐HFS, and DHHFS, was associated with a significant pain relief in patients with failed conventional SCS. This approach is a safe and efficient and should be considered before explantation of the SCS‐system.